Integrating Islamic Values and Sports for Children's Moral Development - Arifin, Andy; Nisak, Nur Maslikhatun (Indonesian Journal of Islamic Studies, 2024)
The general background shows the need for an educational approach that integrates Islamic values and sports activities to shape children's morals holistically. The specific background underscores the importance of this research at TPQ Al-Mu’minun, which teaches the Qur’an and integrates sports into its curriculum. The existing knowledge gap is the lack of in-depth understanding of the impact of integrating Islamic values in sports on children's behavior. The aim of this research is to analyze how this integration affects the morals of children at TPQ Al-Mu’minun. The results show that sports activities such as archery and martial arts enhance children's discipline, responsibility, and ability to manage emotions. The novelty of this research lies in the holistic approach that combines physical and moral aspects in children's education. The implications of these findings indicate that character education that integrates Islamic values and sports can provide significant benefits in shaping positive morals in children, which in turn strengthens their self-confidence, respectful attitudes, and obedience in daily life. Highlights: The integration of Islamic values in sports contributes to the positive development of children's morals. Activities such as archery and martial arts enhance discipline, responsibility, and the ability to manage emotions. The post-activity reflection process deepens children's understanding of Islamic values in their daily lives. Keywords: Integration Islamic Values, Sports, Children's Morals, Character Education, Reflection